SOSIALISASI PENTINGNYA PERAN KADER DALAM MASYARAKAT DI DESA PAREREJA - Tatirah Tatirah (INSTITUT KESEHATAN DELI HUSADA, 2022)
This community service activity is a continuation of the partnership program activities in the Brebes Regency with target partners in Parereja Village, where one of the programs in it is in the health sector, including: high rates of stunting and maternal mortality, lack of awareness about nutrition for pregnant women and toddlers. The parereja village community has 23 health cadres but they are not optimal in health service activities, therefore our role now is to invite the cadres back to remember their roles and functions in the community so that the cadres in parereja village are more empowered and can increase their active role in the community, in addition to it can increase knowledge about the health of the cadres which is increasingly widespread. The method used in this activity is the participatory Rural Appraisal (PRA) method. To achieve this goal, the activities carried out are socialization or counseling and assistance at the local posyandu. The result of this activity is the optimal implementation of health services by cadres to the community.